2010
DOI: 10.1186/1297-9686-42-39
|View full text |Cite
|
Sign up to set email alerts
|

Epistatic QTL pairs associated with meat quality and carcass composition traits in a porcine Duroc × Pietrain population

Abstract: BackgroundQuantitative trait loci (QTL) analyses in pig have revealed numerous individual QTL affecting growth, carcass composition, reproduction and meat quality, indicating a complex genetic architecture. In general, statistical QTL models consider only additive and dominance effects and identification of epistatic effects in livestock is not yet widespread. The aim of this study was to identify and characterize epistatic effects between common and novel QTL regions for carcass composition and meat quality t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…Piétrain) were frequently chosen as one of the founder breeds (Grosse‐Brinkhaus et al . ; Rückert & Bennewitz ). Ledur et al .…”
Section: Results Of the Validation Studiesmentioning
confidence: 99%
“…Piétrain) were frequently chosen as one of the founder breeds (Grosse‐Brinkhaus et al . ; Rückert & Bennewitz ). Ledur et al .…”
Section: Results Of the Validation Studiesmentioning
confidence: 99%
“…2), be capitalized on, in some way, in the Nile tilapia breeding program? While our estimates of epistasis rely upon anonymous loci, a more direct exploitation of epistasis would require identification of the causal variants showing large epistatic interactions [52,53] for each trait. The latter will require substantial resources, probably an order of magnitude greater than resources required for identifying causal variants with additive effects.…”
Section: Use Of the Additive-by-additive Epistatic Effectsmentioning
confidence: 99%
“…However, they estimated non-significant epistatic interactions for these characters. On the other hand, some authors (Uemoto et al, 2009;Groβe-Brinkhaus et al, 2010) suggested that epistasis might be an important component of production traits (including meatness) in pigs. It should be noted that the above mentioned considerable interlocus effects were estimated for crossbred populations.…”
Section: Resultsmentioning
confidence: 99%